2009
DOI: 10.1007/s00431-009-1073-2
|View full text |Cite
|
Sign up to set email alerts
|

Being alive after a severe inorganic mercury intoxication

Abstract: Inorganic mercury intoxication should be considered a potentially life-threatening condition that leads to widespread progressive gastrointestinal, renal, hepatic, hematologic, neuropsychiatric, and dermatologic system hazards. We report here a 10-year-old girl with severe inorganic mercury intoxication whose blood and urine mercury levels were 5,380 microg/L (normal, 0.6 to 59 microg/L) and 91 microg/L (normal, 0.1 to 20 microg/L), respectively, to reveal that life can be saved and complete recovery can be ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 13 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…Fifteen studies, of which 14 are case reports 27,28,29,30,31,32,33,34,35,36,37,38,39,40 and one is cross-sectional 41 , comprising 27 cases, reported some severe hematological effects associated to clinical condition, such as: cerebral or gastrointestinal bleeding related to thrombocytopenia (14) or aplastic anemia (2); multiple organ dysfunction syndrome and leukopenia (2) or hemolytic anemia (2) or aplastic anemia (1); renal insufficiency and thrombocytopenia (2) or leukemoid reaction (1); sepsis and aplastic anemia (2) or neutropenia (1). Mercury biomarker was measured 22 times 29,30,31,32,36,37,38,39,40,41 out of 27 and was always high according to values reported by the authors.…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen studies, of which 14 are case reports 27,28,29,30,31,32,33,34,35,36,37,38,39,40 and one is cross-sectional 41 , comprising 27 cases, reported some severe hematological effects associated to clinical condition, such as: cerebral or gastrointestinal bleeding related to thrombocytopenia (14) or aplastic anemia (2); multiple organ dysfunction syndrome and leukopenia (2) or hemolytic anemia (2) or aplastic anemia (1); renal insufficiency and thrombocytopenia (2) or leukemoid reaction (1); sepsis and aplastic anemia (2) or neutropenia (1). Mercury biomarker was measured 22 times 29,30,31,32,36,37,38,39,40,41 out of 27 and was always high according to values reported by the authors.…”
Section: Resultsmentioning
confidence: 99%
“…It has been a preferred metal for experimentation in chemistry and other science laboratories in schools. Mercury exposure that occurs at poorly ventilated areas such as school or home can be potentially toxic and can cause serious harm and even death [1,6]. Significant exposure to all forms of mercury can result in a variety of health problems including neurological, renal, respiratory, immune, dermatologic, and developmental sequelae.…”
Section: Introductionmentioning
confidence: 99%
“…In the Discussion section, the authors state that "...... findings of hemolysis disappeared rapidly which was consisted with inorganic mercury intoxication" [1]. It has been reported that both inorganic mercury (mercuric mercury, Hg 2+ ) and organic mercury (methyl mercury, CH 3 Hg + ) are able to induce rapid hemolysis in human erythrocyte in vitro [2].…”
mentioning
confidence: 99%
“…Dear Editor, The interesting short report of Erkek et al [1] describes a 10-year-old girl with inorganic mercury intoxication, possibly because of inorganic mercury overexposure while attempting to swim into a creek of cultivated area. Perhaps the reason for very high levels of mercury in the creek waters was due to improper mercury disposal.…”
mentioning
confidence: 99%